Sistem Pendukung Keputusan Pemberian Sanksi Pelanggaran Kedisiplinan Siswa Menggunakan Metode SMART - Qaramathul Puspita Ningrum; Sofiansyah Fadli (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
The purpose of this research is to develop a decision support system that will assist school administrators in administering sanctions for student disciplinary violations. SMART (Simple Multi-Attribute Rating Technique). Through the use of this system, decision-makers (such as Guidance Counselors, School Administrators, Homeroom Teachers) can identify the types of violations, calculate the total violation points, and determine appropriate sanctions based on the calculation results. The application of the SMART method can yield more objective and consistent decisions in dealing with student disciplinary violations. This research highlights the importance of using technology to manage student discipline in schools. It also offers practical solutions that can enhance the efficiency and effectiveness of the disciplinary enforcement process in schools.